Transformational leadership style in rural schools during pandemic: A case study in Indonesian non-WEIRD community - Abdul Aziz; Mohammad Padil; Mujtahid Mujtahid; Kususanto Ditto Prihadi (Institute of Advanced Engineering and Science, 2022)
Studies on the unreadiness of educational stakeholders to face the abrupt requirement of online learning amidst the pandemic were usually conducted among the urban participants with highly available access to the internet and well-developed online social habit. Such population tend to fall into Westernized, Educated, Industrialized, Rich, Democratic (WEIRD) bias population, even in Asian countries. Therefore, their results tend to report problems faced by the aforementioned population. In this current study, we attempt to fill in the population gap by exploring the transformational leadership among school principals in rural area of Malang, East Java, Indonesia. There were five leaders of schools’ setup by different religious affiliations in the community interviewed. After the thematic analyses, the results confirmed that the online learning policy exposed our participants to different problems from the ones faced by the urban population, and therefore they have taken different measures in order to sustain their educational services. Actions such as interschool collaborations, interschool students grouping, and interschool teacher-sharing were introduced to us by these rural school principals, along with the spirit of unity in their diversity. Further exploration and suggestions are discussed in the article.